Sucessão de líderes populistas : um estudo de caso sobre Argentina e Venezuela - Victoria Isabela Frois Borrero (2024)
This work investigates the succession of populist governments, focusing on understanding the factors that influence the authoritarian and/or democratic tendencies of the governments of successors of populist leaders. The research analyzes how the charisma of the populist leader, the process of hybridization of institutions during his government and the contingency factors related to the succession process influence the governments of his successors. The cases of Argentina, with Néstor and Cristina Kirchner, and Venezuela, with Hugo Chávez and Nicolás Maduro, were analyzed using the Historical Comparative Analysis method and process-tracing. The comparative case study allowed us to conclude that the three factors were relevant to explain the authoritarian or democratic tendencies of the governments of the successors of populist leaders, but with different weights. The degree of institutional hybridization and the charisma of the populist leader proved to be more relevant than the specific succession process. The analysis showed that the degree of hybridization of the regime left by populist leaders has a high impact on the successor's government: the greater the degree of hybridization of institutions during the populist government, the greater the authoritarian tendencies of the successor to concentrate power around the Executive. Charisma, in turn, also proved to be relevant, but in different ways: on the one hand, the more the populist leader's government bases its legitimacy on the president's personal charisma, the more difficult it will be for the successor to establish a government considered legitimate, which can encourage the mobilization of authoritarian practices to stabilize power; on the other hand, if the populist leader is successful in routinizing his charisma within institutions and society in a way that makes it impersonal, other leaders are able to benefit from this charisma positively without the need to mobilize authoritarian practices. Finally, the contingency aspects related to succession proved to be relevant, but to a lesser extent: the analyzes indicate that atypical and unpredictable transition situations hinder the ability to build an electorally strong candidacy and reduce the successor's adherence to democratic principles. In short, the case of Venezuela allowed us to see how Chávez's charisma, the process of hybridization during his government and the unusual and unpredictable circumstances of the succession contributed to Maduro's authoritarian tendencies. In turn, in the case of Argentina, Néstor's lack of charisma, the weak hybridization process of his government and the predictable and normal circumstances of government transition contributed to the maintenance of Argentine democracy.